RESPON PERTUMBUHAN DAN HASIL PAKCHOI TERHADAP PENGGUNAAN BIOURINE KAMBING PADA MEDIA GAMBUT - Martati, Martati Umi (Fakultas Pertanian Universitas Tanjungpura, 2020)
This study aimed at getting the best concentrasion of goat biourine to on the growth and yield of pakchoi in peat soils. The research was conducted is located at Kecamatan pontianak Tenggara start from 14th March 2020 until 29th April 2020. The completely Randomized Design (CRD) was used in this experiment with 5 levels concentration of goat biourine with 5 replications. The intended concentration treatment were 50; 75; 100; 125; and 150 ml/l. The observed are variable the root volume, chlorophyll content, leaf area, dry weight of the plant, number of leaves and the fresh weight of the plant. The results showed that the use of goat biourine with a concentration of 100 ml / l showed the highest mean value of all observed variables in the growth and yield of pakchoi by using goat biourine on peat soils media, but the efficient concentrate to on the growth and yield of pakchoi is shown by giving goat biourine 75 ml/l.